2000
DOI: 10.1161/01.str.31.5.1162
|View full text |Cite
|
Sign up to set email alerts
|

The Corticosterone Synthesis Inhibitor Metyrapone Prevents Hypoxia/Ischemia-Induced Loss of Synaptic Function in the Rat Hippocampus

Abstract: Background and Purpose-Ischemia is accompanied by abundant corticosterone secretion, which could potentially exacerbate brain damage via activation of glucocorticoid receptors. We addressed whether manipulating steroid levels during ischemia affects hippocampal synaptic function along with neuronal structure. Moreover, we established whether pretreatment with the glucocorticoid receptor antagonist RU38486 is as effective in preventing deleterious effects after ischemia as is the steroid synthesis inhibitor met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…Prolonged stress or exposure to stress levels of GCs can impair the ability of hippocampal and cortical neurons to survive various insults (Stein-Behrens et al, 1992;Krugers et al, 2000;Madrigal et al, 2003) and can augment insult-induced glutamate release and NMDA receptor activation (Armanini et al, 1990;Moghaddam et al, 1994;Madrigal et al, 2001b). Stress itself can increase glutamate release in both regions and inhibit its uptake by glial transporters (Chou et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged stress or exposure to stress levels of GCs can impair the ability of hippocampal and cortical neurons to survive various insults (Stein-Behrens et al, 1992;Krugers et al, 2000;Madrigal et al, 2003) and can augment insult-induced glutamate release and NMDA receptor activation (Armanini et al, 1990;Moghaddam et al, 1994;Madrigal et al, 2001b). Stress itself can increase glutamate release in both regions and inhibit its uptake by glial transporters (Chou et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Direct effects of glucocorticoids on the motor system might represent one of the pathways mediating the effects of stress on motor recovery after stroke. Earlier studies provide support for this notion by showing that administration of exogenous glucocorticoids (Sapolsky and Pulsinelli, 1985;Sugo et al, 2002), the glucocorticoid receptor antagonist mifepristone (Risedal et al, 1999;Sugo et al, 2002), or the steroid synthesis inhibitor metyrapone (Smith-Swintosky et al, 1997; Krugers et al, 2000) affects the outcome of ischemic lesions in rodents. The relationship between reaching success, recovery and corticosterone levels in the present study was weak, particularly with regard to group differences found in baseline blood samples.…”
Section: Potential Mechanism Of Restraint Stress-induced Functional Imentioning
confidence: 97%
“…Manipulation of circulating stress hormone levels confirms the role of stress in recovery from stroke. Pre-treatment with the corticosteroid synthesis inhibitor metyrapone acts neuro-protectively when given after MCAO in rats (Smith-Swintosky et al, 1997;Krugers et al, 1998Krugers et al, , 2000. In contrast, Risedal et al (1999) found that pre-lesion treatment with metyrapone did not influence infarct size, while post-lesion administration exacerbated infarct volume and motor deficits in rats.…”
Section: Introductionmentioning
confidence: 98%
“…To confirm that GCs (specifically CO) induce functional and morphologic changes in the hippocampus, a GCs synthesis inhibitor, metyrapone 22,23) , was administered to mice, and the effects of the bite-raised condition on Morris water maze training and the number of hippocampal neurons were examined 9) . Metyrapone administered to 9-month-old bite-raised mice attenuated the increase in the blood CO concentration, as well as the impaired performance in the Morris water maze, and hippocampal cell death 9) .…”
Section: Effects Of Gc Antagonists On Bite-raising Induced Impairmentsmentioning
confidence: 99%